Republic of Kenya : Medium Term Debt Management Strategy, 2010/11-2012/13 - Ministry of Finance (Nairobi, 2014)
The objective of debt management in Kenya is to finance the Government financing requirements at the least cost with a prudent degree of risk. The 2010 Medium Term Debt Strategy (MTDS) is a versatile public debt management tool linked to the medium term fiscal framework that contains prudent revenue projections and planned expenditures consistent with Kenya's economic recovery effort. The strategy seeks to address the terms of new borrowing, including the appropriate mix between domestic and external debt. This report explores the objectives of debt management in Kenya, an overview of the previous medium term debt strategy, key developments, characteristics of the existing debt portfolio, outcomes of analysis of strategies, debt sustainability and implementing the 2010 MTDS.